The HARMONIC trial: study protocol for a randomised controlled feasibility trial of Shaping Healthy Minds—a modular transdiagnostic intervention for mood, stressor-related and anxiety disorders in adults. Issue 8 (5th August 2018) - Black, Melissa; Hitchcock, Caitlin; Bevan, Anna; O Leary, Cliodhna; Clarke, James; Elliott, Rachel; Watson, Peter; LaFortune, Louise; Rae, Sarah; Gilbody, Simon; Kuyken, Willem; Johnston, David; et al.
Abstract : Introduction: Anxiety, mood and trauma-related disorders are common, affecting up to 20% of adults. Many of these individuals will experience symptoms of more than one disorder as diagnostically defined. However, most psychological treatments focus on individual disorders and are less effective for those who experience comorbid disorders. The Healthy and Resilient Mind Programme: Building Blocks for Mental Wellbeing (HARMONIC) trial introduces a novel transdiagnostic intervention ( Shaping Healthy Minds (SHM) ), which synthesises several evidence-based treatment techniques to address the gap in effective interventions for people with complex and comorbid difficulties. This early phase trial aims to estimate the efficacy and feasibility of the transdiagnostic intervention in preparation for a later-phase randomised controlled trial, and to explore mechanisms of change. Methods/analysis: We outline a patient-level two-arm randomised controlled trial (HARMONIC) that compares SHM to treatment-as-usual for individuals aged >18 years (n=50) with comorbid mood, anxiety, obsessive-compulsive or trauma/stressor disorders diagnoses, recruited from outpatient psychological services within the UK National Health Service (NHS). The co-primary outcomes will be 3-month follow-up scores on self-report measures of depressive symptoms, anxiety symptoms, and disability and functional impairment. Secondary outcomes include changes in symptoms linked to individual disorders. We will assess the feasibility and acceptability of SHM, the utility of proposed outcome measures, and refine the treatment manuals in preparation for a later-phase trial. Ethics and dissemination: This trial protocol has been approved by the Health Research Authority of the NHS of the UK (East of England, Reference: 16/EE/0095). We anticipate that trial findings will inform future revisions of clinical guidelines for numerous forms of mood, anxiety and stressor-related disorders. Findings will be disseminated broadly via peer-reviewed empirical journal articles, conference presentations, clinical workshops and a trial website. Trial registration: NCT03143634; Pre-results .